A2_4 Moon Migration Weighing You Down? - Bradley-Evans, Ryan; Gafur, Razzia; Heath, Ryan; Hough, Matthew (Physics Special Topics, 2017)
It is theorized the Moon formed approximately 60 Myr after the formation of the Earth during a globally-cataclysmic event widely known as the "Giant Impact Hypothesis". Since its birth, the Moon's distance from Earth has gradually increased as a result of tidal forces. We explore the effect this would have on a 60 kgF human on Earth and find a difference of 0.34 kgF were they to be present across the Moon's history. For the sensation of weightlessness, the Moon would need to orbit about 700 km above the surface of the Earth.